Autonomic Arousal And Experimentally Induced Pain: A Critical Review of the Literature - Brandon N Kyle; Daniel W McNeil (Pain Research and Management)
BACKGROUND: Autonomic arousal frequently is assumed to be a component of the pain response, perhaps because physiological mechanisms connecting pain and autonomic reactivity can be easily conceptualized. The evidence clarifying autonomic responses specific to painful stimulation, however, has been rather sporadic and lacks coherence; thus, a summary and critical review is needed in this area.